The relationship of irisin with metabolic syndrome components and insulin secretion and resistance in schoolchildren. Issue 5 (5th February 2021) - Wu, Chung-Ze; Chu, Nain-Feng; Chang, Li-Chien; Cheng, Chao-Wen; Lin, Yuh-Feng; Pei, Dee; Fang, Te-Chao; Chen, Jin-Shuen
Abstract : Abstract: Irisin, a novel myokine, is believed to be the crucial factor in converting white adipose tissue to beige adipose tissue. For this paper, we studied the relationship among irisin and components of metabolic syndrome (MetS), and insulin secretion and resistance in schoolchildren of Taiwan. Subjects receiving routine annual health examination at elementary school were enrolled. Demographic data, anthropometry, MetS components, irisin, and insulin secretion and resistance were collected. Subjects were divided into normal, overweight, and obese groups for evaluation of irisin in obesity. Finally, the relationship between irisin and MetS was analyzed. There were 376 children (179 boys and 197 girls), aged 10.3 ± 1.5 years, were enrolled. In boys, irisin levels were not associated with body mass index percentile, body fat, blood pressure, lipid profiles, insulin secretion or resistance. After adjusting for age, the irisin level in boys was negatively related to fasting plasma glucose (FPG) ( r = –0.21, P = .006). In girls, after adjusting for age, the irisin levels were positively related only to FPG ( r = 1.49, P = .038). In both genders, irisin levels were similar among normal, overweight, and obese groups, and between subjects with and without MetS. The irisin levels were not associated with MetS in either boys or girls. In girls, circulating irisin levels have a nonsignificant declining trend in overweight and obese girls. However, irisin levels were negatively related to FPG in boys and positively related to FPG in girls. The contrary relationship between irisin and FPG in boys and girls needs further exploration.